Package design. (Cologne : DAAB, 2008)
Despite their at times negative connotation, why do consumers love packaging so much that it has turned into one of the essential conditions for commercial success? Beyond their logistic function of protection, packaging is not only designed to seduce the client and to lead him/her to chose a particular product over another, but it has also become the extension of the brand and the value it embodies. After all, it is the materials enclosing the product, their abundance or absence, colors, shapes and opening techniques that consumers will approve or reject. The 116 examples chosen in this book, be they minimalist or playful, have the same will to resolve the equation of the function of packaging versus the identity of the product it contains in the most original way possible. An index with contact information of the designers is enclosed.
Keywords: Verpakkingen